Balancing Mixed Model Lines with In-Process Inventories - Chakravarty, Amiya K.; Shtub, Avraham (Management Science, 1985)
This paper deals with mixed-model line balancing; i.e., the problem of combining line balancing with lot sizing in a multi-product environment. Recent developments in the area of multi-echelon production/inventory systems are applied, and algorithms are developed which determine the number of work stations required along the line, the tasks assigned to each station, and the cycle time. The algorithms are designed to minimize total production costs composed of labor costs, inventory carrying costs, and setup costs. Computational results are presented to illustrate the ability of the algorithms to design mixed model lines effectively and efficiently.